Implementation of Multisensory Strategies in Arabic Language Learning for Students with Phonological Disorders: A Literature Review - Auliya Ainul Jannah, Ihda; Erlina, Erlina; Ghazi, Fachrul (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study is a literature review aimed at identifying effective instructional strategies for teaching Arabic to students with phonological disorders. Although numerous studies have addressed Arabic language instruction and phonological therapy separately, the integration of the two remains limited. This research adopts a narrative literature review approach by analyzing scholarly articles published between 2020 and 2025, sourced from databases such as Scopus, Google Scholar, ScienceDirect, ResearchGate, and Garuda Kemdikbud. The findings indicate that multisensory strategies, phonology-based phonetic exercises, and the use of interactive technologies (such as audio-visual media and educational applications) are effective in enhancing students' abilities to recognize, differentiate, and produce sounds in Arabic. The review also highlights the importance of individualized interventions and collaboration between teachers and speech therapists in designing inclusive instruction. These findings provide a conceptual foundation for the development of Arabic language instruction that is responsive to the needs of students with special educational needs.